Metal nano array structure controllably prepared on graphene in situ and preparation method of metal nano array structure

Through multi-mode nanotechnology, precisely controlling the deposition of metal nanoparticles on graphene, the problems of deposition instability and difficulty in control in the existing technology are solved, and high-quality metal nanoarray structure is achieved, and the performance of composite materials is improved.

CN119551668AActive Publication Date: 2025-03-04QILU UNIVERSITY OF TECHNOLOGY (SHANDONG ACADEMY OF SCIENCES)
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411740085.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-03-04
Estimated Expiration
2044-11-29

AI Technical Summary

Technical Problem

The prior art is difficult to achieve precise control of the size, morphology, composition, structure and position of metal nanoparticles deposition on graphene, and the deposition stability is insufficient.

Method used

Multimode nanotechnology is adopted to accurately control through atomic force microscopy (AFM), and high-resolution surface morphology images are created, flat and defect-free positions are selected, positive voltage is applied using the tip of the silicon cantilever beam, and the residence time and load are adjusted to make the metal nanomaterial form a metal nanoarray structure on graphene.

Benefits of technology

Accurate control of metal nanoarray structures is achieved, the stability and quality of deposition are improved, and the high-performance application of composite materials is ensured.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119551668A_ABST
    Figure CN119551668A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of nanostructure manufacturing, and discloses a metal nanoarray structure prepared on graphene in an in-situ controllable mode and a preparation method thereof.The preparation method comprises the steps that a silicon wafer serves as a substrate, and a graphene layer is prepared on the silicon substrate through a mechanical stripping method; a silicon cantilever beam containing raw material molecules is installed on an atomic force microscope to scan the prepared substrate, a high-resolution surface topography image is generated, and after a flat position without obvious defects is selected according to the topography image, the tip of the silicon cantilever beam makes contact with the graphene or the surface of the silicon substrate; and then positive voltage is applied to the tip, the retention time and the load are adjusted, so that the metal nanometer material is deposited near the tip, and a metal nanometer array structure is formed. By means of the method, in-situ controllable manufacturing of the size, the morphology, the composition, the structure and the position of the metal particles on the surface of the graphene can be achieved. Therefore, the material can be better popularized and applied in the technical fields of electronics, optics, catalysis, sensing, field emission, display devices and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of nanostructure manufacturing, and in particular, relates to a metal nanoarray structure controllably prepared in situ on graphene and a preparation method thereof. Background Art

[0002] Graphene (GR) is a single-layer carbon atom 2 The two-dimensional material with a honeycomb lattice structure formed by hybrid orbitals has attracted much attention since it was successfully prepared by Geim et al. in 2004. Graphene has excellent properties such as high electrical conductivity, high thermal conductivity, high strength and flexibility, and large specific surface area, making it an ideal carrier for composites. It has shown great application prospects in the fields of electronics, catalysis, sensing, field emission and display devices, nano-optoelectronics, etc.

[0003] With the rapid development of nanotechnology and experimental equipment, the research on graphene's optoelectronics and mechanics has gradually expanded to the research on graphene and various nanomaterials. Since metal nanostructures have high specific strength, high specific modulus, high corrosion resistance, excellent electrothermal properties and excellent processing properties, combining graphene with metal nanomaterials can not only retain the original excellent properties of graphene, but also through the synergistic effect between the two, the composite material can show performance that exceeds that of a single component, which makes graphene / metal nanocomposites a hot topic of research. Among metal nanomaterials, metal nanoparticles (NPs) are more widely used. Metal nanoparticles usually refer to metal crystals or clusters with a diameter of less than 100 nanometers. These particles can be single elements such as gold (Au), silver (Ag), platinum (Pt), etc. or in alloy form.

[0004] Current research shows that metal nanoparticles (NPs) can be deposited on graphene by means of photochemical assisted self-assembly, chemical reduction, thermal evaporation, plasma assisted deposition, etc. For example, the Chinese patent with publication number CN106000377B provides two titanium oxide / graphene nanocomposites, in which the one-dimensional titanium oxide nanotubes and two-dimensional titanium oxide nanosheets prepared in the invention are combined with graphene nanosheets in a paving or layer-by-layer self-assembly manner, and can efficiently remove methylene blue. The composite material is green, environmentally friendly, simple and easy to prepare. However, the means used in the prior art are difficult to achieve precise control of the size, morphology, composition, structure and position of metal nanoparticles deposited on graphene, and the stability of metal nanoparticles deposited on graphene also needs to be improved. Summary of the invention

[0005] In view of the above-mentioned deficiencies in the prior art, an object of the present invention is to provide a metal nanoarray structure that can be controllably prepared in situ on graphene and a preparation method thereof.

[0006] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0007] A method for in-situ controllable preparation of a metal nanoarray structure on graphene comprises the following steps:

[0008] (1) preparing a silicon cantilever beam containing raw material molecules: immersing the silicon cantilever beam in a solution containing raw material molecules, and drying it with filtered compressed gas to form a silicon cantilever beam containing raw material molecules;

[0009] (2) Preparation of silicon substrate: The silicon substrate containing the oxide layer was ultrasonically cleaned with acetone, ethanol, and deionized water in sequence, and then immersed in a strong acid solution to form a clean H + A silicon substrate for the terminal;

[0010] (3) preparing a graphene layer: preparing a graphene layer on the silicon substrate described in step (2) by a mechanical exfoliation method, and performing a plasma controllable treatment on the graphene layer so that the graphene has a certain degree of defect structure;

[0011] (4) Preparation of in-situ controllable metal nanoarray structure on graphene: Preparation is carried out by multi-mode nanotechnology. The silicon cantilever containing raw material molecules prepared in step (1) is first mounted on an atomic force microscope, and the substrate prepared in step (3) is scanned to generate a high-resolution surface morphology image. A flat position without obvious defects is selected based on the morphology image; then the tip of the silicon cantilever is brought into contact with the surface of the graphene or silicon substrate; finally, a positive voltage is applied to the tip, and the dwell time and load are adjusted so that the metal nanomaterial is deposited near the tip to form a metal nanoarray structure.

[0012] The present invention deposits metal nanomaterials on graphene and combines the two, which not only retains the original excellent properties of graphene such as high specific surface area, high conductivity, and good thermal stability, but also enables the composite material to exhibit performance that exceeds that of a single component through the synergistic effect between the two. When the metal nanomaterial is embedded between graphene layers, the interaction force between the graphene layers can be weakened, thereby effectively preventing the stacking and aggregation between the graphene layers and between the metal nanomaterials, while also enhancing the activity of the metal nanomaterial. Among them, the substrate provides a stable physical support platform for the deposition of graphene and metal nanomaterials, ensuring that they will not be easily damaged or fall off during subsequent preparation and application.

[0013] Preferably, in step (1), the raw material molecule is hexachloroplatinic acid; the tip of the silicon cantilever beam is coated with a 25 nm thick layer of platinum-iridium alloy, the spring constant of which is 2.8 N / m and the resonance frequency is 75 kHz.

[0014] Hexachloroplatinic acid (H2PtCl6) is used as a raw material molecule to generate nanoparticles in situ through chemical reactions. By coating the tip of the silicon cantilever with H2PtCl6, it can be ensured that the tip can effectively serve as an electrode to promote the reduction reaction of metal ions during subsequent use. Moreover, the operation is simple and easy, and deposition can be performed by simply applying voltage without the need for additional solution processing steps. The specific reaction formula of the reduction reaction is as follows:

[0015]

[0016] Silicon cantilever is a key component in atomic force microscope (AFM). It is a thin and long silicon chip with one end fixed and the other end free. There is a sharp probe on the cantilever for contacting the sample surface and detecting the morphology and properties of the sample surface through interaction. In the present invention, the silicon cantilever is also used as an electrode for energizing and depositing metal nanomaterials. The platinum-iridium (PtIr) alloy coated on the tip of the silicon cantilever is a coating with good electrochemical activity, high corrosiveness and conductivity, which effectively promotes the reduction reaction of nanometal materials, thereby depositing metal nanomaterials on the graphene layer. Its spring constant refers to the stiffness of the silicon cantilever, which indicates the displacement of the silicon cantilever under the action of unit force. 2.8N / m is a lower value, which means that the silicon cantilever is softer and more sensitive to changes in force; the resonant frequency refers to the frequency at which the silicon cantilever vibrates naturally without external interference; the resonant frequency determines the performance of the silicon cantilever in different operating modes. In mode 1, the silicon cantilever vibrates near the resonant frequency to reduce wear on the sample surface. A higher resonance frequency of 75kHz usually means a faster response speed, which helps to improve the resolution and speed of imaging.

[0017] Preferably, in step (1), the compressed gas is an inert gas, specifically argon; the drying time is 10 to 40 minutes; and the mass percentage of the hexachloroplatinic acid solution is 1 to 10 wt%.

[0018] Preferably, in step (2), the silicon substrate is selected from a p-type silicon wafer, and the thickness of the oxide layer of the silicon substrate is 100 to 400 nm.

[0019] The silicon substrate with a certain oxide layer thickness has stronger mechanical strength and a very flat surface, providing a support platform for the stable attachment of graphene and subsequently deposited metal nanomaterials. The thickness of the oxide layer will affect the transfer quality, electrical properties and subsequent applications of graphene. If the oxide layer is too thick, it will affect the visibility of graphene; if the thickness is too thin, then when the graphene metal nanomaterial is used in electronic devices, it will lead to higher leakage current and lower breakdown voltage, so the preferred thickness is 100 to 400nm. The silicon substrate with a thickness within this range can provide good optical contrast, making graphene easy to observe under a microscope, and because the silicon substrate itself has good thermal conductivity, it can help effectively dissipate heat and promote the conduction of heat from graphene and metal nanomaterials to the silicon substrate, thereby improving the thermal stability of the entire composite material.

[0020] Preferably, the ultrasonic cleaning time in step (2) is 5 to 10 minutes each time, the strong acid solution is a hydrofluoric acid solution, the volume fraction of the hydrofluoric acid solution is 5% to 50%, and the immersion time is 10s to 5min.

[0021] Acetone, ethanol, and deionized water were used to remove organic pollutants on the surface of the silicon substrate, and hydrofluoric acid (HF) solution was used to remove the natural oxide layer on the surface of the silicon substrate. During the subsequent electrochemical deposition, an oxidation reaction occurred on the substrate to form H + The silicon substrate layer as the terminal helps to improve the hydrophilicity of the silicon substrate surface. The electrochemical reactions involved are as follows:

[0022] SiO2+4HF→SiF4+2H2O

[0023] 2H2O-4e - →O2+4H + .

[0024] Preferably, in step (3), the controllable plasma treatment parameters are: oxygen treatment time 30s to 5min, power 20 to 100W.

[0025] Through the controllable plasma treatment of graphene, the graphene surface has a certain defect structure, which increases its hydrophilicity, thereby improving the chemical activity of the material, so that the graphene as a carrier has more active centers, making it easier to react with subsequent metal nanomaterials. The appropriate defect structure can also optimize the flexibility of graphene. The oxygen treatment time of each parameter is controlled to be 30s to 5min, and the power is 20 to 100W. Several carboxyl groups, hydroxyl groups and other groups are introduced on the graphene surface, so that the graphene surface has a certain defect structure, thereby improving its surface hydrophilicity. The treatment time should not be too long, and the power should not be too high to prevent the conductivity from decreasing. The hydrophilicity of the graphene surface is improved while ensuring its conductivity, and it can still form a conductive circuit.

[0026] Preferably, in step (4), the metal nanomaterial is metal nanoparticles (NPs), and the metal nanoparticles are selected from gold, silver, platinum, palladium or copper.

[0027] Metal nanoparticles have a significant surface plasmon resonance (SPR) effect, which is due to the charge accumulation and oscillation effect generated when the nanoparticles interact with light. This effect leads to a strong local electromagnetic field enhancement, which has important applications in optical sensing, surface enhanced Raman scattering (SERS) and other fields; metal nanoparticles also have a high surface area and surface active sites, and are excellent catalysts. When these particles are deposited on graphene, their catalytic activity can be further increased because graphene provides a large specific surface area and good conductivity, which facilitates the rapid transfer of charges and the effective adsorption of reactants.

[0028] Preferably, in step (4), the metal nanoparticles are preferably platinum nanoparticles (NPs).

[0029] Platinum NPs not only have a high specific surface area and abundant active sites, which can significantly improve the efficiency of catalytic reactions, but also have high chemical stability and are not easily oxidized or corroded. This allows platinum NPs to maintain their structure and performance in various chemical environments, making them less likely to fail during long-term use, thus extending their service life. In addition, platinum NPs have low toxicity in vivo and good biocompatibility, so platinum NPs are preferred.

[0030] Preferably, in step (4), the voltage is 8 to 10 V, the dwell time is 7 to 9 s, and the load is 2 to 10 nN.

[0031] The multi-mode nanotechnology provided by the present invention has two modes. Under the action of mode one, AFM can generate high-resolution surface topography images, display the details of the sample surface, and then select a flat area without obvious defects, and then switch to mode two, the tip will directly contact the graphene or silicon substrate surface and slide on the sample surface. This ensures close contact between the tip and the substrate, providing stable conditions for subsequent deposition. Subsequently, the nanostructure is characterized using an energy dispersive spectrometer (EDS) attached to a field emission scanning electron microscope (FESEM, SU8220).

[0032] The specific method of controllable regulation is through controlling the parameters such as voltage, dwell time and load. By adjusting the applied voltage, the reduction rate and deposition amount of metal nano-ions can be controlled; by controlling the dwell time of the tip at each point, the deposition amount in the local area can be controlled; by adjusting the load of the silicon cantilever beam, the contact pressure between the tip and the substrate can be controlled, affecting the formation of the nanostructure.

[0033] Preferably, the temperature in steps (1) to (4) is controlled at 27.2° C. and the humidity is controlled at 37% to 55%.

[0034] The control of temperature and humidity during the whole process is very important for the preparation of metal nanoarrays. The relatively mild temperature provides constant temperature conditions to ensure the consistency of the environment; the humidity is regulated to prevent moisture interference from causing uneven electrochemical reactions or the introduction of impurities. Stable temperature and humidity help ensure the quality and uniformity of the deposited materials and avoid defects or unevenness caused by environmental changes.

[0035] As a general technical concept, the present invention also provides a metal nanoarray structure that is controllably prepared in situ on graphene, and the structure is prepared by any of the above methods.

[0036] Compared with the prior art, the present invention has the following beneficial effects:

[0037] (1) The present invention utilizes multi-mode nanotechnology to achieve high-resolution imaging by precisely controlling the position and dwell time of the AFM tip or the scanning speed, and can control the size, morphology and distribution of platinum nanostructures deposited on graphene and silicon substrates. The formation of metal nanostructures is monitored in real time during the deposition process, and parameters are adjusted in a timely manner to ensure the quality and stability of the array structure. The preparation process is simple and easy to operate.

[0038] (2) The silicon substrate with a certain thickness of oxide layer has high mechanical strength and a very flat surface, which provides a support platform for the stable attachment of graphene and subsequently deposited metal nanoparticles. It can also provide good optical contrast and high thermal conductivity, which helps to quickly dissipate heat, ensuring that heat is transferred from the active area graphene and metal nanoparticles to the substrate, preventing local overheating and enhancing the stability and reliability of the material under high temperature conditions.

[0039] (3) The periodic honeycomb conformation of graphene gives it a high specific surface area and a series of excellent properties, making it an ideal carrier for loading metal nanoparticles. Inserting metal nanoparticles between graphene sheets can reduce the intermolecular forces of graphene sheets, effectively avoid the aggregation of graphene sheets, enhance the overall strength and toughness of the material, and improve the activity of metal nanoparticles, as well as prevent the aggregation of metal nanoparticles. The graphene honeycomb crystal structure can deposit metal nanoparticles more firmly, and is not easy to wear and fall off during subsequent use and operation. In addition, the graphene surface has a certain defect structure through plasma treatment, which increases the hydrophilicity of the graphene surface. By improving the chemical activity of the material, the graphene as a carrier can have more active sites, making it easier to react with the metal nanomaterials added later. At the same time, its conductivity is maintained, making the subsequent electrochemical deposition more uniform, thereby producing a more stable metal nanoarray structure. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 Schematic diagram of the in-situ controllable preparation of metal nanoarray structures on graphene.

[0041] Figure 2 Schematic diagram of the metal nanoarray prepared on graphene in Example 1.

[0042] Figure 3 This is the energy scattering spectrum of platinum NPs prepared on graphene in Example 1.

[0043] Figure 4 This is the morphology of platinum NPs prepared on graphene in Example 1.

[0044] Figure 5 The morphology of platinum NPs prepared on silicon substrates in Comparative Examples 1 to 5.

[0045] The meanings of the main reference numerals in the figures are as follows:

[0046] 1. Silicon cantilever beam, 2. Silicon substrate, 3. Graphene layer, 4. Raw material molecules. DETAILED DESCRIPTION

[0047] The technical solutions in the embodiments of the present invention are described in detail below. The described embodiments are only some embodiments of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field belong to the scope of protection of the present invention. The present invention is further described below with reference to the accompanying drawings in combination with specific embodiments.

[0048] Unless otherwise specified, all materials involved in the present invention can be obtained from commercial channels.

[0049] like Figure 1 As shown, a method for preparing a metal nanoarray structure in situ and controllably on graphene comprises the following steps:

[0050] (1) preparing a silicon cantilever beam 1 containing raw material molecules 4: immersing the silicon cantilever beam 1 in a solution containing raw material molecules 4, and drying it with filtered compressed gas to form a silicon cantilever beam 1 containing raw material molecules 4;

[0051] (2) Preparation of silicon substrate 2: The silicon substrate 2 having an oxide layer of a certain thickness is ultrasonically cleaned with acetone, ethanol, and deionized water in sequence, and then immersed in a strong acid solution to form a clean H + A silicon substrate 2 for terminals;

[0052] (3) preparing a graphene layer 3: preparing a graphene layer 3 on the silicon substrate 2 described in step (2) by a mechanical exfoliation method, and performing a plasma controllable treatment on the graphene layer 3 so that the graphene has a certain degree of defect structure;

[0053] (4) Preparation of in-situ controllable metal nanoarray structure on graphene: Preparation is carried out by multi-mode nanotechnology. The silicon cantilever beam 1 containing the raw material molecule 4 prepared in step (1) is first mounted on an atomic force microscope. The substrate prepared in step (3) is first scanned to generate a high-resolution surface morphology image. A flat position without obvious defects is selected according to the morphology image. The tip of the silicon cantilever beam 1 is then brought into contact with the surface of the graphene layer 3 or the silicon substrate 2. Finally, a positive voltage is applied to the tip, and the dwell time and load are adjusted so that the metal nanomaterial is deposited near the tip to form a metal nanoarray structure.

[0054] The specific embodiments are as follows:

[0055] Example 1

[0056] A method for preparing a metal nanoarray structure in situ and controllably on graphene,

[0057] The following steps are involved:

[0058] (1) A silicon cantilever beam having a spring constant of 2.8 N / m, a resonance frequency of 75 kHz and coated with a 25 nm thick PtIr layer was immersed in a 2 wt% H2PtCl6 solution and dried with filtered compressed argon for 15 min to form a H2PtCl6 coated silicon cantilever beam;

[0059] (2) A p-type silicon wafer with an oxide layer thickness of 300 nm was cleaned in an ultrasonic device with acetone, ethanol, and deionized water for 5 min, and then immersed in a 10% HF solution for 60 s to form a clean HF solution. + A silicon substrate for the terminal;

[0060] (3) preparing a graphene layer on the silicon substrate described in step (2) by a mechanical exfoliation method, and subjecting the graphene layer to plasma treatment, oxygen treatment for 2 min, power of 50 W, so that the graphene has a certain degree of defective structure;

[0061] (4) The H2PtCl6-coated silicon cantilever prepared in step (1) is first mounted on an atomic force microscope, and the substrate prepared in step (3) is first scanned to generate a high-resolution surface morphology image. After selecting a flat position without obvious defects according to the morphology image, the tip of the silicon cantilever is brought into contact with the surface of the graphene or silicon substrate; then a positive voltage of 8 V is applied to the tip, the dwell time is adjusted to 7 s, and a load of 10 nN is set to allow platinum NPs to be deposited near the tip to form a metal nanoarray structure, such as Figure 2 and Figure 3 As shown, platinum NPs are uniformly deposited on the graphene honeycomb crystal structure.

[0062] The temperature was maintained at 27.2°C and the humidity was 45% throughout the process.

[0063] Example 2

[0064] A method for preparing a metal nanoarray structure in situ and controllably on graphene,

[0065] The following steps are involved:

[0066] (1) A silicon cantilever beam having a spring constant of 2.8 N / m, a resonance frequency of 75 kHz and coated with a 25 nm thick PtIr layer was immersed in a 1 wt% H2PtCl6 solution and dried with filtered compressed argon for 10 min to form a H2PtCl6 coated silicon cantilever beam;

[0067] (2) A p-type silicon wafer with an oxide layer thickness of 200 nm was cleaned in an ultrasonic device with acetone, ethanol, and deionized water for 10 min, and then immersed in a 5% HF solution for 30 s to form a clean HF solution. + A silicon substrate for the terminal;

[0068] (3) preparing a graphene layer on the silicon substrate described in step (2) by a mechanical exfoliation method, and subjecting the graphene layer to plasma treatment, oxygen treatment for 1 min, power of 20 W, so that the graphene has a certain degree of defective structure;

[0069] (4) The H2PtCl6-coated silicon cantilever prepared in step (1) is first mounted on an atomic force microscope, and the substrate prepared in step (3) is first scanned to generate a high-resolution surface morphology image. After selecting a flat position without obvious defects according to the morphology image, the tip of the silicon cantilever is brought into contact with the surface of the graphene or silicon substrate; a positive voltage of 9 V is then applied to the tip, the dwell time is adjusted to 7 s, and a load of 6 nN is set to allow platinum NPs to be deposited near the tip to form a metal nanoarray structure.

[0070] The temperature was maintained at 27.2°C and the humidity was 37% throughout the process.

[0071] Example 3

[0072] A method for preparing a metal nanoarray structure in situ and controllably on graphene,

[0073] The following steps are involved:

[0074] (1) A silicon cantilever beam having a spring constant of 2.8 N / m, a resonance frequency of 75 kHz and coated with a 25 nm thick PtIr layer was immersed in a 10 wt% H2PtCl6 solution and dried with filtered compressed argon for 40 min to form a H2PtCl6 coated silicon cantilever beam;

[0075] (2) A p-type silicon wafer with an oxide layer thickness of 400 nm was cleaned in an ultrasonic device with acetone, ethanol, and deionized water for 6 min, and then immersed in a 7% HF solution for 10 s to form a clean HF solution. + A silicon substrate for the terminal;

[0076] (3) preparing a graphene layer on the silicon substrate described in step (2) by a mechanical exfoliation method, and subjecting the graphene layer to plasma treatment, oxygen treatment for 5 min, power of 100 W, so that the graphene has a certain degree of defective structure;

[0077] (4) The H2PtCl6-coated silicon cantilever prepared in step (1) is first mounted on an atomic force microscope, and the substrate prepared in step (3) is first scanned to generate a high-resolution surface morphology image. After selecting a flat position without obvious defects according to the morphology image, the tip of the silicon cantilever is brought into contact with the surface of the graphene or silicon substrate; a positive voltage of 10 V is then applied to the tip, the dwell time is adjusted to 7 s, and a load of 4 nN is set to allow platinum NPs to be deposited near the tip to form a metal nanoarray structure.

[0078] The temperature was maintained at 27.2°C and the humidity was 55% throughout the process.

[0079] Example 4

[0080] A method for preparing a metal nanoarray structure in situ and controllably on graphene,

[0081] The following steps are involved:

[0082] (1) A silicon cantilever beam having a spring constant of 2.8 N / m, a resonance frequency of 75 kHz and coated with a 25 nm thick PtIr layer was immersed in a 5 wt% H2PtCl6 solution and dried with filtered compressed argon for 35 min to form a H2PtCl6 coated silicon cantilever beam;

[0083] (2) A p-type silicon wafer with an oxide layer thickness of 150 nm was cleaned in an ultrasonic device with acetone, ethanol, and deionized water for 8 min, and then immersed in a 40% HF solution for 3 min to form a clean H + A silicon substrate for the terminal;

[0084] (3) preparing a graphene layer on the silicon substrate described in step (2) by a mechanical exfoliation method, and subjecting the graphene layer to plasma treatment, oxygen treatment for 2 min, power of 40 W, so that the graphene has a certain degree of defective structure;

[0085] (4) The H2PtCl6-coated silicon cantilever prepared in step (1) is first mounted on an atomic force microscope, and the substrate prepared in step (3) is first scanned to generate a high-resolution surface morphology image. After selecting a flat position without obvious defects according to the morphology image, the tip of the silicon cantilever is brought into contact with the surface of the graphene or silicon substrate; then a positive voltage of 8 V is applied to the tip, the dwell time is adjusted to 7 s, and a load of 10 nN is set to allow platinum NPs to be deposited near the tip to form a metal nanoarray structure.

[0086] The temperature was maintained at 27.2°C and the humidity was 40% throughout the process.

[0087] Example 5

[0088] A method for preparing a metal nanoarray structure in situ and controllably on graphene,

[0089] The following steps are involved:

[0090] (1) A silicon cantilever beam having a spring constant of 2.8 N / m, a resonance frequency of 75 kHz and coated with a 25 nm thick PtIr layer was immersed in a 3 wt% H2PtCl6 solution and dried with filtered compressed argon for 11 min to form a H2PtCl6 coated silicon cantilever beam;

[0091] (2) A p-type silicon wafer with an oxide layer thickness of 120 nm was cleaned in an ultrasonic device with acetone, ethanol, and deionized water for 7 min, and then immersed in a 20% HF solution for 4 min to form a clean H + A silicon substrate for the terminal;

[0092] (3) preparing a graphene layer on the silicon substrate described in step (2) by a mechanical exfoliation method, and subjecting the graphene layer to plasma treatment, oxygen treatment for 50 seconds at a power of 70 W, so that the graphene has a certain degree of defective structure;

[0093] (4) The H2PtCl6-coated silicon cantilever prepared in step (1) is first mounted on an atomic force microscope, and the substrate prepared in step (3) is first scanned to generate a high-resolution surface morphology image. After selecting a flat position without obvious defects according to the morphology image, the tip of the silicon cantilever is brought into contact with the surface of the graphene or silicon substrate; then a positive voltage of 8 V is applied to the tip, the dwell time is adjusted to 8 s, and a load of 4 nN is set to allow platinum NPs to be deposited near the tip to form a metal nanoarray structure.

[0094] The temperature was maintained at 27.2°C and the humidity was 38% throughout the process.

[0095] Example 6

[0096] A method for preparing a metal nanoarray structure in situ and controllably on graphene,

[0097] The following steps are involved:

[0098] (1) immersing a silicon cantilever beam having a spring constant of 2.8 N / m, a resonance frequency of 75 kHz and coated with a 25 nm thick PtIr layer into a H2PtCl6 solution having a mass proportion of 8 wt%, and drying it with filtered compressed argon for 26 min to form a silicon cantilever beam coated with H2PtCl6;

[0099] (2) A p-type silicon wafer with an oxide layer thickness of 250 nm was cleaned in an ultrasonic device with acetone, ethanol, and deionized water for 9 min, and then immersed in a 15% HF solution for 40 s to form a clean HF solution. + A silicon substrate for the terminal;

[0100] (3) preparing a graphene layer on the silicon substrate described in step (2) by a mechanical exfoliation method, and subjecting the graphene layer to plasma treatment, oxygen treatment for 2 min, power of 30 W, so that the graphene has a certain degree of defective structure;

[0101] (4) The H2PtCl6-coated silicon cantilever prepared in step (1) is first mounted on an atomic force microscope, and the substrate prepared in step (3) is first scanned to generate a high-resolution surface morphology image. After selecting a flat position without obvious defects according to the morphology image, the tip of the silicon cantilever is brought into contact with the surface of the graphene or silicon substrate; then a positive voltage of 8 V is applied to the tip, the dwell time is adjusted to 10 s, and a load of 4 nN is set to allow platinum NPs to be deposited near the tip to form a metal nanoarray structure.

[0102] The temperature was maintained at 27.2°C and the humidity was 42% throughout the process.

[0103] Comparative Example 1

[0104] A method for preparing a metal nanoarray structure in situ and controllably on a silicon substrate.

[0105] The following steps are involved:

[0106] (1) A silicon cantilever beam having a spring constant of 2.8 N / m, a resonance frequency of 75 kHz and coated with a 25 nm thick PtIr layer was immersed in a 2 wt% H2PtCl6 solution and dried with filtered compressed argon for 15 min to form a H2PtCl6 coated silicon cantilever beam;

[0107] (2) A p-type silicon wafer with an oxide layer thickness of 300 nm was cleaned in an ultrasonic device with acetone, ethanol, and deionized water for 5 min, and then immersed in a 10% HF solution for 60 s to form a clean silicon substrate with H+ as the terminal;

[0108] (3) The H2PtCl6-coated silicon cantilever prepared in step (1) is first mounted on an atomic force microscope, and the substrate prepared in step (2) is first scanned to generate a high-resolution surface morphology image. After selecting a flat position according to the morphology image, the tip of the silicon cantilever is then brought into contact with the surface of the silicon substrate; a positive voltage of 4 V is then applied to the tip, the scanning speed is adjusted to 50 nm / s, and a load of 10 nN is set to allow platinum NPs to be deposited near the tip.

[0109] The temperature was maintained at 27.2°C and the humidity was 45% throughout the process.

[0110] Comparative Example 2

[0111] A method for preparing a metal nanoarray structure in situ and controllably on a silicon substrate.

[0112] The following steps are involved:

[0113] (1) A silicon cantilever beam having a spring constant of 2.8 N / m, a resonance frequency of 75 kHz and coated with a 25 nm thick PtIr layer was immersed in a 4 wt% H2PtCl6 solution and dried with filtered compressed argon for 21 min to form a H2PtCl6 coated silicon cantilever beam;

[0114] (2) A p-type silicon wafer with an oxide layer thickness of 240 nm was cleaned in an ultrasonic device with acetone, ethanol, and deionized water in sequence for 7 min, and then immersed in a 24% by volume HF solution for 55 s to form a clean silicon substrate with H+ as the terminal;

[0115] (3) The H2PtCl6-coated silicon cantilever prepared in step (1) is first mounted on an atomic force microscope, and the substrate prepared in step (2) is first scanned to generate a high-resolution surface morphology image. After selecting a flat position according to the morphology image, the tip of the silicon cantilever is then brought into contact with the surface of the silicon substrate; a positive voltage of 4 V is then applied to the tip, the scanning speed is adjusted to 40 nm / s, and a load of 10 nN is set to allow platinum NPs to be deposited near the tip.

[0116] The temperature was maintained at 27.2°C and the humidity was 47% throughout the process.

[0117] Comparative Example 3

[0118] A method for preparing a metal nanoarray structure in situ and controllably on a silicon substrate.

[0119] The following steps are involved:

[0120] (1) A silicon cantilever beam having a spring constant of 2.8 N / m, a resonance frequency of 75 kHz and coated with a 25 nm thick PtIr layer was immersed in a 5 wt% H2PtCl6 solution and dried with filtered compressed argon for 33 min to form a H2PtCl6 coated silicon cantilever beam;

[0121] (2) A p-type silicon wafer with an oxide layer thickness of 230 nm was cleaned in an ultrasonic device with acetone, ethanol, and deionized water in sequence for 6 min, and then immersed in a 25% by volume HF solution for 15 s to form a clean silicon substrate with H+ as the terminal;

[0122] (3) The H2PtCl6-coated silicon cantilever prepared in step (1) is first mounted on an atomic force microscope, and the substrate prepared in step (2) is first scanned to generate a high-resolution surface morphology image. After selecting a flat position according to the morphology image, the tip of the silicon cantilever is then brought into contact with the surface of the silicon substrate; a positive voltage of 4 V is then applied to the tip, the scanning speed is adjusted to 30 nm / s, and a load of 10 nN is set to allow platinum NPs to be deposited near the tip.

[0123] The temperature was maintained at 27.2°C and the humidity was 41% throughout the process.

[0124] Comparative Example 4

[0125] A method for preparing a metal nanoarray structure in situ and controllably on a silicon substrate.

[0126] The following steps are involved:

[0127] (1) A silicon cantilever beam having a spring constant of 2.8 N / m, a resonance frequency of 75 kHz and coated with a 25 nm thick PtIr layer was immersed in a 4 wt% H2PtCl6 solution and dried with filtered compressed argon for 36 min to form a H2PtCl6 coated silicon cantilever beam;

[0128] (2) A silicon wafer with an oxide layer thickness of 240 nm was cleaned in an ultrasonic device with acetone, ethanol, and deionized water for 7 min, and then immersed in a 45% HF solution for 36 s to form a clean HF solution. + A silicon substrate for the terminal;

[0129] (3) The H2PtCl6-coated silicon cantilever prepared in step (1) is first mounted on an atomic force microscope, and the substrate prepared in step (2) is first scanned to generate a high-resolution surface morphology image. After selecting a flat position according to the morphology image, the tip of the silicon cantilever is then brought into contact with the surface of the silicon substrate; a positive voltage of 4 V is then applied to the tip, the scanning speed is adjusted to 20 nm / s, and a load of 10 nN is set to allow platinum NPs to be deposited near the tip.

[0130] The temperature was maintained at 27.2°C and the humidity was 53% throughout the process.

[0131] Comparative Example 5

[0132] A method for preparing a metal nanoarray structure in situ and controllably on a silicon substrate.

[0133] The following steps are involved:

[0134] (1) A silicon cantilever beam having a spring constant of 2.8 N / m, a resonance frequency of 75 kHz and coated with a 25 nm thick PtIr layer was immersed in a 2 wt% H2PtCl6 solution and dried with filtered compressed argon for 24 min to form a H2PtCl6 coated silicon cantilever beam;

[0135] (2) A p-type silicon wafer with an oxide layer thickness of 280 nm was cleaned in an ultrasonic device with acetone, ethanol, and deionized water for 10 min, and then immersed in a 16% HF solution for 45 s to form a clean H + A silicon substrate for the terminal;

[0136] (3) The H2PtCl6-coated silicon cantilever prepared in step (1) is first mounted on an atomic force microscope, and the substrate prepared in step (2) is first scanned to generate a high-resolution surface morphology image. After selecting a flat position according to the morphology image, the tip of the silicon cantilever is then brought into contact with the surface of the silicon substrate; a positive voltage of 4 V is then applied to the tip, the scanning speed is adjusted to 10 nm / s, and a load of 10 nN is set to allow platinum NPs to be deposited near the tip.

[0137] The temperature was maintained at 27.2°C and the humidity was 51% throughout the process.

[0138] From the morphology images of the platinum NPs prepared in Examples 1 to 6 and Comparative Examples 1 to 5, the height and diameter data are extracted, as shown in Table 1:

[0139] Table 1 Height and diameter values ​​of platinum NPs prepared in Examples 1 to 6 and Comparative Examples 1 to 5

[0140] Height(nm) Diameter(nm) Example 1 1.91±0.54 24.68±6.30 Example 2 2.14±0.63 28.78±7.41 Example 3 3.01±0.39 34.03±5.64 Example 4 3.27±1.45 35.07±6.23 Example 5 3.49±1.69 40.25±2.36 Example 6 4.34±2.01 43.08±5.68 Comparative Example 1 2.35±1.05 70.45±7.34 Comparative Example 2 3.87±2.04 80.25±3.45 Comparative Example 3 4.12±0.98 95.24±6.28 Comparative Example 4 5.56±1.25 100.21±4.25 Comparative Example 5 9.48±1.23 105.23±4.12

[0141] Combined with Table 1, Figure 4 As with Examples 1 to 3, the size change of platinum NPs was tested by changing the voltage. As the voltage increased, the height and diameter of the platinum NPs also increased, which means that the size of the platinum NPs increased with the increase of the voltage, because the rate of the reduction reaction is directly affected by regulating the voltage. A higher voltage will increase the electric field strength, thereby accelerating the reduction reaction of platinum ions, so that more platinum ions are reduced to platinum atoms and deposited on graphene, thereby forming larger-sized nanoparticles. The maximum height of the platinum NPs formed was 3.01±0.39nm, and the maximum diameter was 34.03±5.64.

[0142] Combining Table 1 with Examples 4 to 6, this is an experiment to test the size change of platinum NPs by changing the residence time. As the residence time increases, the height and diameter of the platinum NPs also increase, which means that the size of the platinum NPs increases with the increase in residence time, and compared with Examples 1 to 3 in which the voltage is changed, the size change of the platinum NPs is more obvious, and the growth rate is also greater. The minimum height of the platinum NPs formed in Examples 4 to 6 is 3.27±1.45, and the minimum diameter is 35.07±6.23, both of which are larger than the size of the platinum NPs prepared in Examples 1 to 3. By adjusting the residence time, the residence time of the tip on the substrate is changed. A longer residence time means that more platinum ions have more time to be reduced and deposited at this position. The longer the residence time, the larger the platinum NPs formed.

[0143] Combining Table 1 with Examples 1 to 5 and Comparative Examples 1 to 6, it is found that as the load changes, the change in load has a certain effect on the platinum NPs, but the effect is not significant.

[0144] Combining Table 1 with Comparative Examples 1 to 5, since it only contains a silicon substrate and no graphene layer, the height and diameter of the prepared platinum NPs are significantly larger than those of Examples 1 to 6, that is, the size of the platinum NPs directly deposited on the silicon substrate is larger, but the large-sized platinum NPs will reduce the overall specific surface area, reduce the surface activity, and further reduce the catalytic activity and adsorption capacity of the material; when the particle size increases to a certain extent, the movement of electrons is no longer significantly restricted, and the energy level changes from discrete to continuous. This leads to the weakening or disappearance of the quantum size effect, thereby affecting the optical, electrical and magnetic properties of the material. Combining Figure 5 , we can see that larger nanoparticles are more likely to agglomerate and form larger aggregates. Agglomeration further reduces the specific surface area and may block active sites, thereby reducing the performance of the material.

[0145] In summary, the method for preparing a metal nanoarray provided by the present invention can accurately and flexibly adjust the size, morphology and position of metal nanoparticles deposited on graphene by adjusting the voltage and residence time, so that it can be better applied to electronic devices, catalysis, sensor technology, energy conversion, optical applications, biomedicine and other fields.

[0146] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the technical principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for in-situ controllable preparation of a metal nanoarray structure on graphene, characterized in that: The following steps are involved: (1) preparing a silicon cantilever beam containing raw material molecules: immersing the silicon cantilever beam in a solution containing raw material molecules, and drying it with filtered compressed gas to form a silicon cantilever beam containing raw material molecules; (2) Preparation of silicon substrate: The silicon substrate containing the oxide layer was ultrasonically cleaned with acetone, ethanol, and deionized water in sequence, and then immersed in a strong acid solution to form a clean H + A silicon substrate for the terminal; (3) preparing a graphene layer: preparing a graphene layer on the silicon substrate described in step (2) by a mechanical exfoliation method, and performing a plasma controllable treatment on the graphene layer so that the graphene has a defective structure; (4) Preparing an in-situ controllable metal nanoarray structure on graphene: The preparation is carried out by multi-mode nanotechnology, firstly the silicon cantilever containing the raw material molecules prepared in step (1) is mounted on an atomic force microscope, the substrate prepared in step (3) is scanned to generate a high-resolution surface morphology image, and a flat position without obvious defects is selected according to the morphology image; then the tip of the silicon cantilever is brought into contact with the surface of the graphene or silicon substrate; Finally, a positive voltage is applied to the tip, and the dwell time and load are adjusted to allow the metal nanomaterial to be deposited near the tip to form a metal nanoarray structure.

2. The method for in-situ controllable preparation of a metal nanoarray structure on graphene according to claim 1, characterized in that: In the step (1), the raw material molecule is hexachloroplatinic acid; the tip of the silicon cantilever beam is coated with a 25 nm thick layer of platinum-iridium alloy, the spring constant of which is 2.8 N / m and the resonance frequency is 75 kHz.

3. The method for in-situ controllable preparation of a metal nanoarray structure on graphene according to claim 1, characterized in that: In the step (1), the compressed gas is an inert gas, specifically argon; the drying time is 10 to 40 minutes; and the mass percentage of the hexachloroplatinic acid solution is 1 to 10 wt%.

4. The method for in-situ controllable preparation of a metal nanoarray structure on graphene according to claim 1, characterized in that: In the step (2), the silicon substrate is selected from a p-type silicon wafer, and the thickness of the oxide layer of the silicon substrate is 100 to 400 nm.

5. The method for in-situ controllable preparation of a metal nanoarray structure on graphene according to claim 1, characterized in that: The ultrasonic cleaning time in step (2) is 5 to 10 minutes each time, the strong acid solution is a hydrofluoric acid solution, the volume fraction of the hydrofluoric acid solution is 5% to 50%, and the immersion time is 10s to 5min.

6. The method for in-situ controllable preparation of a metal nanoarray structure on graphene according to claim 1, characterized in that: In the step (3), the parameters of the controllable plasma treatment are: oxygen treatment time 30s to 5min, power 20 to 100W.

7. The method for in-situ controllable preparation of a metal nanoarray structure on graphene according to claim 1, characterized in that: In the step (4), the metal nanomaterial is metal nanoparticles, and the metal nanoparticles are selected from gold, silver, platinum, palladium or copper.

8. The method for in-situ controllable preparation of a metal nanoarray structure on graphene according to claim 1, characterized in that: In the step (4), the voltage is 8 to 10 V, the dwell time is 7 to 9 s, and the load is 2 to 10 nN.

9. The method for in-situ controllable preparation of a metal nanoarray structure on graphene according to claim 1, characterized in that: The temperature in steps (1) to (4) is controlled at 27.2° C. and the humidity is controlled at 37% to 55%.

10. A metal nanoarray structure controllably prepared in situ on graphene, characterized in that: The method is prepared by any one of claims 1 to 9.

Citation Information

Patent Citations

  • Two types of titanium dioxide / graphene nanocomposites

    CN106000377B

  • Nano-electromechanical resonant sensor based on graphene sheet layer and manufacturing method thereof

    CN102538949A

  • Nanocomposite material preparation method based on graphene oxide autocatalysis

    CN102557021A

  • Graphene-clad atomic force microscope probe and manufacturing method and application thereof

    CN104360107A

  • Method for quickly preparing large-area graphene / metal composite structure surface enhanced Raman scattering substrate

    CN107037032A